Windmill‐Like Nanogenerator for Harvesting Low‐Speed Wind Energy and Wind Speed Measuring. Issue 9 (29th March 2022) - Zhu, Xiaoyu; Cao, Xia; Wang, Zhong Lin
Abstract: Wind energy, one of the most promising and renewable energy sources, is extensively exploited around the world. However, in traditional triboelectric nanogenerator (TENG) for wind energy harvesting, due to the limitations of device structures with high friction force, the collection of wind energy at low speeds is always faced with enormous challenges. To overcome this difficulty, an ultralow friction and highly effective windmill‐like nanogenerator (WNG) is proposed. Herein, the WNG is based on a freestanding mode TENG and adopts a rotational triboelectric layer with contact–separation mode. This special design successfully achieves a smaller friction resistance, allowing wind energy to be captured at low speeds. Under the minimum wind speed, the optimized WNG has a maximum load power of 0.753 µW, which can illuminate nine LEDs simultaneously. The WNG can convert wind energy into enough electricity to power a hygrometer or a digital clock under the maximum wind speed. Moreover, a wind speed detection system based on WNG is developed and proves the superiority of real‐time wind speed detection by appropriate computation parameters. This work not only shows the development potential of the WNG in low‐speed wind energy collection but also expends the application potential of TENG‐based self‐powered environmental monitoring. Abstract : Triboelectric nanogenerators (TENG) can convert environmental wind energy into electricity. However, some rely on high wind speeds to work, and the wind speed detection is only performed by output. In this article, the TENG proposed has the superiority in harvesting low‐speed wind energy and constructing a wind speed detection system through a microcontroller unit.